Aviation Developers Worldwide: Constructors and Aviators (1900–1914) - Sollinger, Guenther (History of Engineering Sciences and Institutions of Higher Education, 2023)
Despite speculations long back in history, heavier-than air flight made its breakthrough during the first decade of the 20th century, based on the designs and practical experiments of at first a handful of constructors in Europe and the United States. Already by early 1911, the activities of several thousand aviators, including the constructors of airplanes, attracted not only wide public attention but also the interest of military establishments. The article analyzes significant data – nationality, profession, military rank, date and location of certification, location of airplane operations, domestic and foreign airplane types, and fatalities – for 13 369 constructors and aviators from 51 countries worldwide who were active between 1900 and 1914. Added to this group are the constructors of helicopters, ornithopters, gliders, and other flying apparatuses, resulting in a total of 14 142 individuals.